Distributed Photovoltaic Island Monitoring Method Based on Gated Loop Unit - Ao, Jianyong; Li, Yanping; Li, Zhukun (IEEE ... Information Technology and Mechatronics Engineering Conference (ITOEC ... ) (Online), 2025)
The rapid deployment of distributed photovoltaic (PV) systems has introduced new challenges in islanding detection, a critical task for grid stability and safety. This paper presents a novel Distributed Photovoltaic Island Monitoring Method Based on Gated Loop Unit (GLU). The GLU leverages advanced signal processing and dynamic response mechanisms to enhance detection sensitivity and accuracy. The proposed distributed architecture enables real-time data acquisition and collaborative decision-making across PV nodes, ensuring reliable monitoring under diverse grid conditions. Simulations and case studies validate the method's effectiveness, demonstrating superior performance in terms of detection accuracy, low latency, and robustness when compared to conventional techniques. The proposed approach provides a scalable and efficient solution for improving islanding detection in distributed PV systems, contributing to the development of resilient and intelligent power grids.